Discourse Analysis of Media in Web-version News - et.al, Prof. Dr.Qasim Obayes Al-Azzawi , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
News contributes a lot to the modern life regarding the way of conveying the information . Different institutions work in making news so affective and to attract people's attention . Therefore , new is one of the means of modern press . This kind of the text is built on a number of the factors to make the message that the news convoys more attractive . One of these ways that contribute to such a matter is cohesion . Cohesion plays a key role in the way of forming the text . Accordingly , the text follows certain linguistic techniques . The study focuses on two aspects of the cohesion the lexical one and grammatical one . The study has found that not all of these devices are used to show the cohesion of the text . The value of the study is that the journalists must follow these tools in writing the news and these tools help the journalists in the field of the press or journalism . The study is important because the study sheds light on the one of the aspects of making the news and this aspect is crucial . The model of the study is based on (Halliday and Hassan , 1976) . The study has found that the use of certain grammatical devices and lexical ones is very influential in building the influential pieces of news.